Pain Measurement through Temperature Changes in Children Undergoing Dental Extractions - Eleazar S. Kolosovas-Machuca; Mario A. Martínez-Jiménez; José L. Ramírez-GarcíaLuna; Francisco J. González; Amaury J. Pozos-Guillen; Nadia P. Campos-Lara; Mauricio Pierdant-Perez (Pain Research and Management)
Background and Objective. Pain evaluation in children can be a difficult task, since it possesses sensory and affective components that are often hard to discriminate. Infrared thermography has previously been used as a diagnostic tool for pain detection in animals; therefore, the aim of this study was to assess the presence of temperature changes during dental extractions and to evaluate its correlation with heart rate changes as markers of pain and discomfort. Methods. Thermographic changes in the lacrimal caruncle and heart rate measurements were recorded in healthy children scheduled for dental extraction before and during the procedure and compared. Afterwards, correlation between temperature and heart rate was assessed. Results. We found significant differences in temperature and heart rate before the procedure and during the dental extraction (mean difference 4.07°C, p<0.001, and 18.11 beats per minute, p<0.001) and no evidence of correlation between both measurements. Conclusion. Thermographic changes in the lacrimal caruncle can be detected in patients who undergo dental extractions. These changes appear to be stable throughout time and to possess very little intersubject variation, thus making them a candidate for a surrogate marker of pain and discomfort. Future studies should be performed to confirm this claim.